STATISTICAL USE OF ACCOUNTING INFORMATION IN FEDERAL ECONOMIC POLICY FORMATION. - Cooper, William W. (The Accounting Review, 1948)
Abstract The article discuss recent developments in the statistical utilization of accounting data by the federal government. In particular, attention will be focused on the statistical utilization of accounting information for what may be called top-policy purposes. Most accountants are familiar to some extent with the utilization of accounting data by various federal agencies for direct administrative purposes. In the administration of tax laws and for regulatory bodies, accounting data have proved indispensable for handling individual cases. Moreover, most accountants are probably familiar with the fact that individual case information is frequently compiled into statistical information as a means of orienting agency policy, setting standards, and serving as a basis for recommendations to the U.S. Congress. In a sense various recent developments in business financial statistics represent extensions of accounting to new areas of great importance. These extensions require the development of new techniques and point of view, and it is hoped that the instrumentalities of classification and analysis made possible by accounting will gain in the process. Full utilization of the potentialities of accounting will occur, however, only if accountants can be persuaded to take a continuing interest in these developments and to acquire the necessary familiarity with the problems involved to adapt their techniques to the requirements.